Estimation of the leaf area index from Sentinel images in Eucalyptus grandis W.Hill plantations - Rudy Solís-Silvan; Facundo Sanchez-Gutiérrez; Raúl Enrique Islas-Jesús; José del Carmen Gerónimo-Torres; César Orlando Pozo-Santiago; Baltazar Sanchez-Díaz (Tecnología en Marcha, 2022)
Eucalyptus grandis plantations are of great importance, from a social point of view due to their great commercial value, and from an ecological point of view because they are capable of harboring a certain biodiversity of species. The leaf area index (LAI) is an important indicator to measure the health of these plantations related to productivity. The objective of this research is to estimate the LAI from Sentinel images in Eucalyptus grandis plantations. Sentinel satellite images were used to estimate the LAI in the plantations, later the statistical analyzes were carried out by means of a comparison of independent means. Values ​​were obtained as the mean that was 2.0 of the leaf area index in the plantations, these results were very similar to those obtained in other investigations carried out in the field. Therefore, it is recommended to use this methodology in other types of plantations, since it can be used to be applied in other equations to calculate the potential yield of crops.